THE PRINCIPAL'S POLICY IN ENHANCING TEACHERS' UNDERSTANDING OF THE MERDEKA CURRICULUM AT MTS YAPDI - Harahap, Yusuf Ali Ahmad; Mesiono, Mesiono (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to understand the forms of school principals' policies, the strategies of school principals, the supporting and inhibiting factors, as well as the impact of school principals' policies in enhancing teachers' understanding of the independent curriculum at MTs YAPDI. Using a Qualitative Descriptive Approach, the data collection methods include: observation, interviews, and documentation. The data were analyzed using an interactive analysis model. The results show that the school principal's policy in enhancing teachers' understanding of the curriculum is very enthusiastic in involving teachers in every training, workshop, or seminar related to the independent curriculum, both offline and online/in-house (IHT). The principal also implements a gradual and sustainable approach along with mentoring for teachers in each class. The principal also facilitates and involves teachers in planning learning during subject teachers' discussions (MGMP), in the implementation of the independent curriculum, and finally conducts regular evaluation meetings for educators at MTs YAPDI. In addition, there are supporting factors such as easy access to the internet and the fact that the teachers are mostly young individuals who are very adept at using social networks. The WKM also assists the principal by developing programs related to learning, managing budgets for training and teacher resources, and providing support to teachers by granting them freedom and facilitating them. The inhibiting factors include, among others, the lack of synchronization in the timing of training for subjects relevant to the available independent curriculum, causing some teachers to miss out on the opportunity, resulting in a minimal understanding of the independent curriculum among teachers. The last obstacle is the limited facilities and infrastructure.